2017
DOI: 10.1097/qad.0000000000001412
|View full text |Cite
|
Sign up to set email alerts
|

Elevated cytomegalovirus IgG antibody levels are associated with HIV-1 disease progression and immune activation

Abstract: Objective To assess the association between CMV IgG antibody levels, HIV disease progression, and immune activation in sub-Saharan Africa. Design A prospective cohort study was conducted among women enrolled in a trial that was designed to determine the effect of acyclovir on HIV disease progression in Rakai, Uganda. Methods The primary endpoints were progression to a CD4+ T-cell count<250 cells/μL, non-traumatic death, or initiation of ART. CD4+ T-cell counts, HIV viral load, C-reactive protein, and solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…In our study, an association between CMV-specific T-cell response and anti-CMV IgG antibodies was observed with higher level of anti-CMV IgG antibodies in immunodiscordant individuals (Gómez-Mora et al ., PLOS ONE. Accepted Manuscript) and in line with a recent study, where an association between CMV IgG levels and disease progression has been reported 27 . It has been demonstrated that circulating anti-CMV IgG antibodies and CMV-specific T-cell responses are associated with cardiovascular diseases and physical function impairment 23 , 25 , 26 , 43 , suggesting that in HIV + individuals with poor CD4 + T-cell recovery the high CMV-specific response, probably due to episodes of CMV reactivation mainly in the genital tract 41 , 44 , may have an impact in the higher mortality and morbidity observed in those individuals.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, an association between CMV-specific T-cell response and anti-CMV IgG antibodies was observed with higher level of anti-CMV IgG antibodies in immunodiscordant individuals (Gómez-Mora et al ., PLOS ONE. Accepted Manuscript) and in line with a recent study, where an association between CMV IgG levels and disease progression has been reported 27 . It has been demonstrated that circulating anti-CMV IgG antibodies and CMV-specific T-cell responses are associated with cardiovascular diseases and physical function impairment 23 , 25 , 26 , 43 , suggesting that in HIV + individuals with poor CD4 + T-cell recovery the high CMV-specific response, probably due to episodes of CMV reactivation mainly in the genital tract 41 , 44 , may have an impact in the higher mortality and morbidity observed in those individuals.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, CMV has been described as a major contributor to the increased immune activation and senescence in HIV + individuals with poor CD4 + T-cell recovery 20 22 . Furthermore, increased CMV-specific antibodies and/or T-cells have been associated with atherosclerosis and impaired CD4 + T-cell reconstitution and progression in HIV-infected individuals on treatment 23 – 27 . However, CMV-specific T-cell responses in individuals with poor CD4 + T-cell recovery have not been completely characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The precise mechanism by which HBV, HCV, and CMV coinfections may have deleterious effects on CD4 + T-cell count recovery is unclear. The impaired immunological recovery in HBV-, HCV-, or CMV-coinfected patients could be due to the destruction of CD4 + T cells by coinfection-mediated CD4 + T-cell activation, apoptosis, or exhaustion [145][146][147][148][149]. Others studies did not show an association between HBV,142,150,151 HCV,152,153 or CMV 154 coinfection and immunological recovery.…”
mentioning
confidence: 99%
“…CMV infection is prevalent in Africa and may contribute to a lower vaccine response observed in this population. Furthermore, CMV co-infection has been associated with faster disease progression and elevated CMV-specific IgG antibody levels in untreated HIV-infected individuals, further contributing to disease progression and immune activation [ 42 ]. For patients receiving long-term antiretroviral therapy (ART), CMV-co-infection remains an independent contributor to persistent CD8 T-Cell expansion and inflammation [ 43 ].…”
Section: Infection Aging and Vaccine Responsementioning
confidence: 99%